Analysing teaching-learning interactions in higher education accounting for structure and agency - Ashwin, Paul (Continuum, 2012)
This book offers critical insight into existing perspectives on researching teaching and learning in higher education and argues that alternative perspectives are required in order to account for structure and agency in teaching-learning interactions in higher education.